Entre a ciência e a crença: discursivizações sobre a AIDS na mídia impressa de São Luís-Ma na década de 1980 - FREITAS, Camila Cutrim Lins de (2020)
This work analyzes how the printed media, in São Luís (MA), produced meanings about AIDS in four newspapers of great circulation in the 1980s: Jornal da Cidade, Jornal Pequeno, O Imparcial and O Estado do Maranhão. Through a discursive plurality, crossed by speeches from different fields of knowledge, including medical-scientific knowledge and religious knowledge, the print media in São Luís produced meanings about the disease and helped to build the history of AIDS in Brazil. City. Adopting the Foucaultian molds of research, we will treat the media as a device, according to the notion of Foucault (2000) and AGAMBEN (2010), because it is capable of originating, in dialogue with various discourses, such as medicine, new forms of subjectivities . For our discussions, in addition to Foucault's postulates, we rescued GREGOLIN (2004), which helped us to understand how French Discourse Analysis is born and is perpetuated. To understand how AIDS becomes an event in newspapers and in social life and in New History, we look for NORA (1986) and LE GOFF (1996). To serve as the basis of our analysis, the newspaper O Globo was used to better understand how AIDS was treated in Brazil so that, later, we could better understand it in the Ludovicense discourse. In the third chapter, we use PELBART (2007) and the notions about power and biopolitics; BUTLER (2019) and MILANEZ (2007) to understand how biopolitics affects sick bodies. According to our analysis, these newspapers treat the disease as an evil, a plague, as a consequence of the country's moral debauchery. Even the biomedical speeches were taken by extra-scientific conceptions that detract from any neutrality. As Bessa (1997, p. 14) points out, “AIDS goes beyond the biomedical field. Thus, it is not only a health crisis, but it also becomes a crisis of the word, of the discourses ”. To describe and analyze the discursive web that has been created about the disease is also to reveal problems in its history.